Developing Cultural Awareness Curricular Competencies for Humanitarian Non-Governmental Organization Staff. Issue 6 (1st December 2021) - Hart, Alexander; Toma, Mariana; Issa, Fadi; Neault, Noelle
Abstract: Background: Cultural awareness is an important part of organizational success when interacting with multiple cultures. Research has shown a dearth of standardized cultural awareness training programs for non-governmental humanitarian organization staff. Purpose: This study aims to develop an expert-consensus set of cultural awareness competencies as the basis for development of humanitarian staff cultural awareness trainings. Methods: A modified Delphi process was selected. The first round of surveys collected a list of cultural awareness competencies from experts in the fields of non-governmental organization (NGO) operations and cultural awareness education and research. This collated list of competencies was then used as the basis of a survey obtaining ratings by the group on a five-point Likert scale. Competencies which achieved an average rating of 4.0 or higher were considered to be "important" for inclusion in future training programs. Results: A total of 67.9% of contacted experts agreed to participate, with 84.2% of those completing all rounds of the survey. This group developed a list of ten competencies, including: Cultural Awareness/Sensitivity and Intercultural Communication; Cultural Intelligence; Unconscious Bias/Diversity Awareness; a Universal Declaration of Ethical Principles; Gender and Lesbian, Gay, Bisexual, Transgender, Queer, and Other Sexual Identities (LGBTQ+) Issues and Safety; Analytical and Critical Thinking Skills; Negotiation; Program Mission; Power Dynamics; and Empathy. Conclusions: This study defined a set of ten expert-consensus cultural awareness competencies which can be a basis for future NGO staff training. Future work can both use these competencies to create educational programs and further define and expand the set of competencies based on analyses of their implementation.